TxNxM1 The Anatomy and Clinics of Metastatic Cancer - Debois, J. M. (Springer Netherlands, 2002)
Although distant metastases are the most dreaded situation in the evolution of cancer of every organ, the medical literature has surprisingly given little attention to the anatomical relationship between the primary tumor and metastasic sites. Only risk factors, treatment possibilities, and survival results are extensively examined. Stimulated by the occurrence in his practice of some puzzling and unexpected metastases, the author reviewed more than 12,000 references. He looked for anatomical relationships highlighting the relation between the location of the primary tumors and the particular patterns of metastasis observed. It would seem that the `pathways and flows' are apparently a more decisive factor in the implantation of the metastases than the `seed and soil' properties of the cancer cells and the metastatic site. Aided by his colleague Dr. T. Geukens, M.D., the author includes original anatomical drawings, illustrating the sometimes unexpected pathways the cancer cells follow in order to reach the organs where they will become lodged and give rise to metastatic tumors. The subject has apparently not been exhausted in the literature and several ideas are given for further research.